THE PRACTICE OF MORAL SUFISM AT DAYAH TUHFATUL BAIDHA AL-AZIZIYAH (MAHFAD ATJEH) - Luqmanul Hakim; Damanhuri; Ernita Dewi (Indonesian Journal of Islamic and Social Science, 2025)
The purpose of this study is to understand the ethical Sufism practiced at Dayah Tuhfatul Baidha Al-Aziziyah. The research uses a qualitative method with a phenomenological approach, aiming to explore the experiences and understanding of the students regarding the practice of ethical Sufism. Data was collected through observation, interviews, and document analysis. Based on the research findings, it is known that Dayah Tuhfatul Baidha Al-Aziziyah actively implements the practice of ethical Sufism as an integral part of education and the daily life of the students. The results of this study indicate that the ethical Sufism practiced at Dayah Tuhfatul Baidha Al-Aziziyah plays a key role in shaping better individuals. Within this Dayah environment, the practice of ethical Sufism is not only a series of relations between Allah and His servants, but also a path to cultivate various virtues and morality. Finally, the results of this study are expected to provide insights that A deeper understanding of the practice of ethical Sufism at Dayah Tuhfatul Baidha Al-Aziziyah (Mahfad Atjeh) as well as the procedures for practicing ethical Sufism, which are carried out daily by the students through various obligatory acts of worship, solely with the aim of seeking the pleasure of Allah. Keywords: Practice, Ethical Sufism, Dayah Tuhfatul Baidha Al-Aziziyah